Variasi Morfologi Arachnothera longirostra (Passeriformes, Nectariniidae) (Latham, 1790) - Aldino Fauzil Fanani; Wilson Novarino; Djong Hon Tjong (Universitas Andalas, 2012)
Research about morphological variation of Arachnothera longirostra (Passeriformes, Nectariniidae) on Harapan Rainforest (Jambi), The Biological Education and Research Forest (BERF) and Marapi Mount have been conducted from September 2011 to February 2012. The samples have been collected directly on the field and data were analyzed on Animal Taxonomy Laboratory, Biology Departement, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. Based on the (analysis) result using Kruskall-Wallis Test, the females were found five of nine variation morphological characters and the males were found seven characters. Based on Mann-Whitney U test was found one character that appeared consistenly different to females such as WDTB (Wide Bill), while for males were found two characters such as WDTB (Wide Bill) and LGTR (Long Tarsus). Phenogram obtained by UPGMA analysis showed close relationship between populatiaon of A. longirostra from both of Marapi and HPPB populations.Keywords: morphology, variation, nectariniidae, Arachnothera longirostra